Epitaxial growth of TbFe2 on piezoelectric LiNbO3 Z-cut. (12th March 2020) - Polewczyk, Vincent; Hehn, Michel; Hillion, Arnaud; Robert, Sylvie; Boulet, Pascal; Dumesnil, Karine
Abstract: The strongly magnetostrictive TbFe2 compound has been epitaxially grown on Z-cut Lithium Niobate (LiNbO3 ) substrates after the deposition of various buffer layers (Mo, Ti and Ti/Mo). Detailed and combined RHEED and x-ray analysis permitted to unravel the in-plane and relative orientation relationships (OR) of the different materials in the system. Despite the use of different templates with different structural orders, similar final OR are eventually found between the piezoelectric substrate and the magnetic layer. The structural and magnetic properties are analyzed in order to get a TbFe2 layer of optimum quality to build a magnetostrictive/piezoelectric hybrid system with efficient strain mediated coupling. Such systems are of interest for the development of magnetic sensors as well as for the electric control of magnetization.